A Prospective Study on Child Morbidity and Gut Microbiota in Rural Malawi. Issue 4 (October 2019) - Kortekangas, Emma; Young, Rebecca; Cheung, Yin B.; Fan, Yue-Mei; Jorgensen, Josh M.; Kamng'ona, Arox W.; Chaima, David; Ashorn, Ulla; Dewey, Kathryn G.; Maleta, Kenneth; Ashorn, Per
ABSTRACT: Objectives: The determinants of gut microbiota composition and its effects on common childhood illnesses are only partly understood, especially in low-income settings. The aim of the present study was to investigate whether morbidity predicts gut microbiota composition in Malawian children and whether microbiota predicts subsequent morbidity. We tested the hypothesis that common infectious disease symptoms would be predictive of lower microbiota maturity and diversity. Methods: We used data from 631 participants in a randomized-controlled nutrition intervention trial, in which a small-quantity lipid-based nutrient supplement was provided to pregnant and lactating mothers and their children at 6 to 18 months of age. Fecal samples were collected from the children at 6, 12, 18, and 30 months of age and analyzed using 16S rRNA sequencing. Microbiota variables consisted of measures of microbiota diversity (Shannon Index), microbiota maturity (microbiota-for-age z score), and the relative abundances of taxa. Morbidity variables included gastrointestinal and respiratory symptoms and fever. Results: Diarrhea and respiratory symptoms from 11 to 12 months were predictive of lower microbiota-for-age z score and higher Shannon Index, respectively ( P = 0.035 and P = 0.023). Morbidity preceding sample collection was predictive of the relative abundances of several bacterial taxa at all time points. Higher microbiota maturity and diversity at 6 months were predictive of a lower incidence rate of fever in the subsequent 6 months ( P = 0.007 and P = 0.031). Conclusions: Our findings generally do not support the hypothesis that morbidity prevalence predicts a subsequent decrease in gut microbiota maturity or diversity in rural Malawian children. Certain morbidity symptoms may be predictive of microbiota maturity and diversity and relative abundances of several bacterial taxa. Furthermore, microbiota diversity and maturity may be associated with the subsequent incidence of fever. Abstract : Supplemental Digital Content is available in the text